ANALISIS TINGKAT KEPUASAN KARYAWAN TERHADAP FASILITAS GEDUNG BARU DI PT KUKAR MANDIRI SHIPYARD - Az-Zahrahani Ramadhani; Fareis Althalets (BORJUIS: JURNAL OF ECONOMY, 2026)
The physical work environment operates as a fundamental determinant of employee satisfaction, psychological well-being, and organizational productivity, particularly within the high-stakes sectors of heavy manufacturing and maritime logistics. This exhaustive study evaluates the level of employee satisfaction regarding the newly renovated head office building facilities at PT Kukar Mandiri Shipyard, a leading maritime enterprise located at Jl. Mulawarman No. 10, Samarinda, East Kalimantan. Utilizing a quantitative descriptive approach, primary data was meticulously collected through a structured questionnaire administered to 19 administrative and structural employees across vital departments, including Finance, Purchasing, Accounting, and Administration. The empirical results demonstrate a highly positive overall perception of the new physical infrastructure. Indicators such as building cleanliness, spatial arrangement, ergonomic lighting, and physical security achieved near-perfect mean scores (ranging from 4.89 to 4.95 on a 5-point Likert scale). Nevertheless, a critical vulnerability was identified concerning the air circulation and ventilation indicator, which recorded the lowest mean score (4.21) alongside the highest statistical variance. This specific deficiency indicates a decline in Indoor Air Quality (IAQ), potentially exacerbated by the necessity to seal the building against external urban air pollution and traffic emissions. The comprehensive analysis confirms that the optimization of physical facilities significantly elevates perceived comfort, work enthusiasm, and self-reported productivity, perfectly aligning with Herzberg’s Two-Factor Theory wherein hygiene factors effectively neutralize workplace dissatisfaction. Strategic recommendations are directed towards mitigating indoor air quality impediments to secure long-term employee retention and optimize human capital sustainability.